HIGH FREQUENCY REGENERATION PROTOCOL FOR CALLUS CULTURES OF PEANUT LEAVES USING ETHYLENE MODULATORS AS CULTURE MEDIUM ADDITIVE - T. RADHAKRISHNAN; O. JITHESH; J. R. DOBARIA (The Bioscan, 2014)
In order to develop high frequency regeneration protocols in peanut exploiting ethylene modulators, influence of four ethylene modulators viz. ethrel, silver nitrate, cobalt chloride and putrescine were studied on the regeneration behavior of immature leaves of peanut. Ethrel was found to inhibit the development in vitro. The addition of silver nitrate had enhanced the number of shoot buds regenerated per explant and hence could be used as a regular culture medium additive in peanut. Cobalt chloride was also found to increase the frequency of regeneration in peanut. The variation in the response induced by putrescine was also wider than the other additives. It was concluded that silver nitrate is the best ethylene modulator among the four additives studied and its use in culture medium at a level 0.01mM enhanced the regeneration frequency from the immature leaves of the peanut irrespective of the genotype used. In the new method of acclimatization developed by combining the rooting and hardening steps, prolonged growing of the plants on culture medium could be avoided. In this method no mortality was observed during the process of acclimatization. This method can be exploited in the nodal culture from field grown plants also without having the hazels of surface sterilizing the explants.